The experience of low-income men with prostate cancer transitioning from disease-specific coverage to comprehensive insurance under the affordable care act. (December 2018) - Nabhani, Jamal A.; Vargas, Grecia; Kwan, Lorna; Connor, Sarah E.; Fink, Arlene; Maliski, Sally L.; Litwin, Mark S.
Highlights: Insurance coverage transitions induced anxiety in men with prostate cancer. Men faced challenges scheduling timely appointments and language barriers with insurance under the ACA. Social support, health educational resources, and navigation services are valued by men with prostate cancer. Disease-specific models of care may pay dividends going forward and provide sufficient care for select populations. Abstract: Purpose: To describe the insurance enrollment process under the Affordable Care Act (ACA) for a vulnerable population of previously uninsured men with prostate cancer. To understand tradeoffs between high-touch (patient navigation, education, and counseling services) disease-specific coverage and comprehensive insurance for low-income men with prostate cancer. Apply beneficial concepts from each to inform higher quality coverage for patients with cancer. Methods: Analysis of 27 semi-structured interviews with men transitioning from California's IMPACT (Improving Access, Counseling and Treatment for Californians with Prostate Cancer) program to insurance under the ACA. Results: We identified six themes: 1) Concerns about gaps in care and confusion about ongoing IMPACT eligibility, 2) Applying for insurance was aided by participants' families and enrollment resources, 3) Men missed IMPACT's social support, 4) Men sought new sources for patient education, 5) New challenges arose accessing and navigating care with insurance, and 6) The transition to insurance financially benefitted men with chronic conditions most. Conclusions: Taken together, the results support the integration of disease-specific coverage transition plans, social support, navigation, and educational services into insurance benefits. In the face of resource constraints, disease-specific coverage models may provide critical access to medical services for select populations.